2007
DOI: 10.1002/jbm.a.30998
|View full text |Cite
|
Sign up to set email alerts
|

Pullulan‐based hydrogel for smooth muscle cell culture

Abstract: A hydrogel was prepared from pullulan and evaluated as a novel biomaterial for vascular engineering. Using a crosslinking process with sodium trimetaphosphate in aqueous solution, homogeneous, transparent, and easy-to-handle pullulan gels were obtained with water-content higher than 90%. A circular punch was used to cut 6-mm diameter and 2-mm thickness discs for cell culture. Environmental scanning electron microscopy analysis of hydrated gels revealed a smooth surface, on which rabbit vascular smooth muscle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 17 publications
1
65
0
Order By: Relevance
“…We have previously reported the biocompatibility of STMP cross-linked polymer scaffolds in vitro and in vivo in rats. [28][29] The new process by crosslinking with STMP and progressive evaporation, described here for the first time, constitutes an original procedure that endows the PVA with very particular features. The mechanisms of the STMP cross-linking reaction for hydroxylated polymers, such as polysaccharides, have been recently described by Lack et al [30] Phosphoesterification of hydroxyl residues is the main reaction, leading to the formation of phosphoester bridges and phosphate hanging groups, which are negatively charged, favoring a high hydration.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the biocompatibility of STMP cross-linked polymer scaffolds in vitro and in vivo in rats. [28][29] The new process by crosslinking with STMP and progressive evaporation, described here for the first time, constitutes an original procedure that endows the PVA with very particular features. The mechanisms of the STMP cross-linking reaction for hydroxylated polymers, such as polysaccharides, have been recently described by Lack et al [30] Phosphoesterification of hydroxyl residues is the main reaction, leading to the formation of phosphoester bridges and phosphate hanging groups, which are negatively charged, favoring a high hydration.…”
Section: Discussionmentioning
confidence: 99%
“…These natural polymers hold promise for healing and regenerating damaged tissues, since they are highly permeable and facilitate the transport of nutrients and metabolites [46]. Here, a macroporous matrix was used, composed of the natural hydrophilic polysaccharides pullulan and dextran, which have already been used in cell therapy [47,48]. Their suitability has been proved for vascular cell growth [49] and for culturing MSCs from adipose tissue [50].…”
Section: Introductionmentioning
confidence: 98%
“…In fact, we showed that, with higher heparin content, the release of VEGF was more sustained in VEGF2 than VEGF1 scaffolds. The crosslinking of pullulan and dextran using STMP is hypothesized to occur through the formation of intermolecular phosphate linkages [29,30], which can also trap the positively charged VEGF. Yet this may be unlikely to occur, since a recent study by Purnama et al showed that plain PD scaffolds loaded with VEGF before freeze-drying exhibited rapid release within 24 h without any marked release thereafter for the next 2 days [31].…”
Section: Discussionmentioning
confidence: 99%